The world book student discovery encyclopedia (Chicago, 2000)
A general elementary encyclopedia with brief illustrated articles covering an alphabetical array of topics. The world book student discovery encyclopedia provides pronunciation for many unusual or unfamiliar words. In the pronunciation, the words are divided into syllables and respelled according to the way each syllables,...
Keywords: Encyclopedias and dictionaries,Children’s encyclopedias and dictionaries